RADICALIZATION AND EXTREMISM OF YOUTH: COMPARATIVE CASE STUDY OF PALESTINE AND ISRAEL - Dobrucka, Weronika (The Policy of National Security, 2024)
The Israeli-Palestinian conflict, one of the most prolonged and most severe in modern times, is a source of violence, hatred and acts of terrorism that affect the daily lives of both societies. Particularly susceptible to this negative impact are young people, who, in response to various factors, develop a system of reactions, including a turn toward extremist views and radicalization. This increases mutual resentment, hostility and acts of violence, disrupting already poorly functioning social relations. This paper examines these processes on youth in Israel and Palestine and aims to identify the mechanisms leading to them on both sides. The analysis highlights how the creation of the State of Israel in 1948 and the subsequent territorial disputes fueled by Zionist ideologies have perpetuated cycles of violence and retribution. Using a qualitative comparative case study approach, the author analyzes cultural, educational and religious influences and direct interactions with the authorities or educators on youth from both sides. Great importance was given to social or economic factors, as lack of prospects, dehumanization, or social rejection are among the most critical factors pushing young people toward radicalization. Additional emphasis is also placed on the influence of stereotyping of the Hamas terrorist organization, as well as mandatory service in IDF units. The paper also addresses trauma and mental health as some of the factors that influence the development of aggressive behaviour. The findings underscore the complexity of the radicalization process, influenced by multiple interrelated factors and emphasize the need for strategies to prevent youth radicalization in Israel and Palestine and promote peace in the region.
Keywords: Israeli-Palestinian conflict; radicalization; extremism; Middle East; Israel; Palestine